2019
DOI: 10.5014/ajot.2019.73s1-po6005
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Families With a Young Child With Pediatric Autoimmune Neuropsychiatric Disorder Associated With Streptococcal Infection (PANDAS)

Abstract: Date Presented 04/05/19 PANDAS is the abrupt onset of OCD or tics after streptococcal infection in a formerly healthy child. We used qualitative phenomenology to explore family quality of life (FQOL) in six families with a child who developed PANDAS in early childhood. Data were collected through interviews, which were transcribed and analyzed through a rigorous inductive process. Results indicate that PANDAS severely impacts FQOL, and OT's awareness of PANDAS may be key to supporting the child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…This indicates only mild to moderate impairments in sensory functioning relative to peers (Parham & Ecker, 2007). This finding is in contrast with those of Tona et al (2017) and Demchick et al (2019) who reported cases of severe disturbances in sensory reactivity, specifically related to tactile sensitivities that rendered clothing intolerable. For example, a participant in Demchick et al's (2019, p. 191) study on family quality of life in the context of raising a child with PANS stated that it took a parent '…three hours to get out of the house due to her daughter's severe sensory sensitivity with clothing …'.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This indicates only mild to moderate impairments in sensory functioning relative to peers (Parham & Ecker, 2007). This finding is in contrast with those of Tona et al (2017) and Demchick et al (2019) who reported cases of severe disturbances in sensory reactivity, specifically related to tactile sensitivities that rendered clothing intolerable. For example, a participant in Demchick et al's (2019, p. 191) study on family quality of life in the context of raising a child with PANS stated that it took a parent '…three hours to get out of the house due to her daughter's severe sensory sensitivity with clothing …'.…”
Section: Discussioncontrasting
confidence: 99%
“…6) noted that their child with PANS was '…unable to wear any clothes for days because of extreme tactile defensiveness …'. The difference between our findings and those reported by Tona et al (2017) and Demchick et al (2019) suggests that there is an inherent variability in the sensory experiences of children during PANS exacerbations. Some children may experience only mild sensory symptoms during periods of exacerbation, whereas others may experience sensory symptoms that are severe and incapacitating.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations